2018
DOI: 10.1177/2192568218754512
|View full text |Cite
|
Sign up to set email alerts
|

Age Is a Risk Factor for Postoperative Complications Following Excisional Laminectomy for Intradural Extramedullary Spinal Tumors

Abstract: Study Design: Retrospective analysis. Objective: The incidence of intradural extramedullary (IDEM) spinal tumors is increasing. Excisional laminectomy for removal and decompression is the standard of care, but complications associated with patient age are unreported in the literature. Our objective is to identify if age is a risk factor for postoperative complications after excisional laminectomy of IDEM spinal tumors. Methods: A retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
(114 reference statements)
0
3
0
1
Order By: Relevance
“…Primary spinal cord tumor is rare in patients, and for this reason, the relevant statistics are still lacking ( 1 ). It was reported that the incidence of primary spinal cord tumor (PSCT) was 10–15 times less than that of primary intracranial tumors, which accounts for ~5–15% of all spinal tumors and 2–4% of all primary tumors of the central nervous systems (CNS) ( 2 , 3 ). According to the anatomical location, PSCT can be classified as extradural, intradural extramedullary, and intramedullary ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primary spinal cord tumor is rare in patients, and for this reason, the relevant statistics are still lacking ( 1 ). It was reported that the incidence of primary spinal cord tumor (PSCT) was 10–15 times less than that of primary intracranial tumors, which accounts for ~5–15% of all spinal tumors and 2–4% of all primary tumors of the central nervous systems (CNS) ( 2 , 3 ). According to the anatomical location, PSCT can be classified as extradural, intradural extramedullary, and intramedullary ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 Previous studies have investigated the outcomes of spinal tumor surgery and identified factors commonly associated with postoperative morbidity and mortality. [12][13][14][15][16][17][18][19][20][21][22][23] However, these studies were either retrospective institutional studies applicable only to specific groups of tumors or procedures [12][13][14]16,[18][19][20][21][22][23] or analyzed a limited number of predictors or outcome measures. [12][13][14][15][16][17][18][19][20][21]23 A comprehensive risk score that incorporates preoperative AE predictors could help surgeons anticipate major postoperative AEs.…”
mentioning
confidence: 99%
“…12-23 However, these studies were either retrospective institutional studies applicable only to specific groups of tumors or procedures 12-14,16,18-23 or analyzed a limited number of predictors or outcome measures. 12-21,23 A comprehensive risk score that incorporates preoperative AE predictors could help surgeons anticipate major postoperative AEs.…”
mentioning
confidence: 99%
“…Ушкодження хребців в результаті неопластичних процесів призводить до тяжких наслідків стану здоров'я різного віку та статі [1,2]. Наслідком невірно обраної тактики лікування первинних та метастатичних уражень хребта є тяжкі ортопедо-неврологічні ускладнення і, навіть, летальний результат [3,4]. На теперішній час є можливим виконання об'єму хірургічного втручання від малоінвазивного до «total en block» [5,6].…”
unclassified